Penglibatan Negara-Negara Islam Dalam Misi Pengaman Antarabangsa : Islamic Countries Participation In International Peacekeeping Mission - Muhammad Afifi Abdul Razak; Kamarul Azman Khamis; Rusdi Omar; Mashitah Mohd Udin (Online Journal of Research in Islamic Studies, 2021)
International peacekeeping mission is an important mechanism in the aspect of contemporary international conflict management. Since its first implementation by United Nations (UN) wayback in 1948, it attracted interest and participation from many countries in the organization. This includes the Islamic countries. Since the end of the Cold War era in the late 1980s, Islamic countries emerged as among the leading participant and troop contributor to international peacekeeping mission especially the mission organized by the UN. Half of the top-ten troop contributors to the current UN mission today are the Islamic countries such as Bangladesh, Pakistan, Egypt, Indonesia and Ghana. Even though Islamic countries had been contributing actively in numerous UN missions, nothing much were known about it. This article discussed in brief about the scenario of Islamic countries participation in international peacekeeping mission by referring to the mission organized by the UN and non-UN organizations since its early years to the present time. The approach use in this article are historical analysis and content analysis. This article concluded that, firstly, this scenario served as an evidence of Islamic countries un-ending support to the UN as a world governing body; secondly, national interest and not religious interest seems to be the primary driving factor of Islamic countries participation in peacekeeping; and finally, while Islamic countries continued its active participation in this areas of contribution, it nevertheless had to familiarize itself with the impacts and challenges that it currently faced which maybe will limited its noble effort to continue its support to international peacekeeping mission in the near future.